Animo Bertani di Kalangan Generasi Muda di Desa Bandungan Kecamatan Bulango Utara Kabupaten Bone Bolango - Alipu, Regina; Musa, Farid Th.; Harold, Rudy (Department of Sociology, Faculty of Social Sciences, Gorontalo State University, Indonesia, 2024)
Agriculture in Indonesia is currently facing a problem: the decreasing number of young people willing to take over roles from the older generation in the agricultural sector. The purpose of this research is to understand the interest of the younger generation in agriculture, both in terms of attraction and lack thereof. This study employs methods to comprehend the situation by collecting data through observation, interviews, and documentation. The research results indicate that, first, many young people are not interested in farming because they view agriculture as an unpromising, outdated profession that does not align with their lifestyle. Second, several factors influencing the lack of interest among the younger generation in farming include the low prestige associated with agriculture, an imbalance between the agricultural process and its unsatisfactory outcomes, the influence of the surrounding environment, the emergence of new subcultures in the digital era, and a lack of knowledge and support for agriculture.